Evaluation of Upper Abdominal Pain of Admitted Patients in a Tertiary Hospital (The Planet, 2022)
Background: Abdominal pain is an extremely common presenting symptom. Within this upper abdominal pain that is located in epigastrium or either hypochondriac is more commoner one. This pain may arise from upper abdominal structures like stomach, Liver, Gall bladder etc. Objectives: The main objective of this study is to evaluate the upper abdominal pain of patients admitted in a tertiary hospital. Method: This prospective study was conducted at Holy Family Red Crescent Medical College Hospital, Dhaka, Bangladesh for a period of March 2008 to February 2009. The cases were selected by special inclusion and exclusion criteria. All patients were presented with acute upper abdominal pain. The age group of the patients is mostly belong to younger and forabdominal pain and diseases female age group is mostly affected in this series. The study was designed to treat all the patients conservatively and accordingly all were given conservative regimen up to 24 hours. There after they were assessed clinically. Result: In this study 200 cases of upper abdominal pain from Bangladesh. series 22% patient is anaemic, 52% shows epigastric tenderness, positive Murphy’s sign found in 14% cases. Rt hypochondriac tenderness was present in 20% cases. Other less common clinical finding was hepatomegaly (5%), Jaundice (4%) and wt. loss (2.5%).In this series I/V fluid was mostly used for the treatment protocol. The other protocol such as PPI/H2 blocker, triple therapy, antibiotics was also used for the protocol. Antispicasmodics were the second most used treatment used for the diseases of upper abdominal pain. The outcome of the cases was excellent with 1% death and no patient leaving hospital of their own in the present series. Conclusion: In this series there is a strong association between age of the patient, duration of acute illness and outcome. It is suggested that treatment of selected cases of upper abdominal pain and its related diseases should be improved for every sex groups specially those who are mostly affected by these diseases.
Keywords: Abdominal Pain; Diseases